Articles and lectures by Florence O'Donoghue on guerilla warfare including O'Donoghue's ‘Guerilla warfare in Ireland 1919-1921’, delivered to Dublin Historical Association and published in 'An Cosantóir', 1963, with associated correspondence and notes, - O'Donoghue, Florence, 1895-1967 (1962)
Includes May 1963 and July 1964 issues of 'An Cosantóir'.